Mesophyll Chloroplast Investment in C3, C4 and C2 Species of the Genus Flaveria. (16th March 2016) - Stata, Matt; Sage, Tammy L.; Hoffmann, Natalie; Covshoff, Sarah; Ka-Shu Wong, Gane; Sage, Rowan F.
Abstract : The mesophyll (M) cells of C4 plants contain fewer chloroplasts than observed in related C3 plants; however, it is uncertain where along the evolutionary transition from C3 to C4 that the reduction in M chloroplast number occurs. Using 18 species in the genus Flaveria, which contains C3, C4 and a range of C3 –C4 intermediate species, we examined changes in chloroplast number and size per M cell, and positioning of chloroplasts relative to the M cell periphery. Chloroplast number and coverage of the M cell periphery declined in proportion to increasing strength of C4 metabolism in Flaveria, while chloroplast size increased with increasing C4 cycle strength. These changes increase cytosolic exposure to the cell periphery which could enhance diffusion of inorganic carbon to phosphenolpyruvate carboxylase (PEPC), a cytosolic enzyme. Analysis of the transcriptome from juvenile leaves of nine Flaveria species showed that the transcript abundance of four genes involved in plastid biogenesis— FtsZ1, FtsZ2, DRP5B and PARC6 —was negatively correlated with variation in C4 cycle strength and positively correlated with M chloroplast number per planar cell area. Chloroplast size was negatively correlated with abundance of FtsZ1, FtsZ2 and PARC6 transcripts. These results indicate that natural selection targeted the proteins of the contractile ring assembly to effect the reduction in chloroplast numbers in the M cells of C4 Flaveria species. If so, efforts to engineer the C4 pathway into C3 plants might evaluate whether inducing transcriptome changes similar to those observed in Flaveria could reduce M chloroplast numbers, and thus introduce a trait that appears essential for efficient C4 function.